Meta-Analysis: The Effectiveness of Using Blended Learning on Multiple Intelligences and Student Character Education During the Covid-19 Period - Karlini Oktarina; Suhaimi Suhaimi; Tomi Apra Santosa; Abdul Razak; Irdawati Irdawati; Yuni Ahda; Lufri Lufri; Dwi Hilda Putri (Universitas Muhammadiyah Mataram, 2021)
This study aims to determine the effectiveness of the use of integrated blended learning on multiple intelligences (multiple intelligence) and student character education during the COVID-19 period. This type of research is a meta-analysis research. The research sample came from a search of 21 national and international journals. Search articles through databases sourced from Google Scholar, Eric, IEEE, Science Director and Wiley. The sample selection technique is purposive sampling technique. The data sampled relates to the use of Blended Learning, Multiple Intelligence and character education. Data analysis used quantitative data analysis techniques by conducting effect size and N-Gain tests using JASP software version 26. The results showed that the use of STEM integrated blended learning was effective in increasing students' multiple intelligence with an average value of 76.25 and student character education of 75 with the value of effect size (ES) is 0.44 and the N-Gain is 0.65 category medium.